LAPAROSCOPIC AND OPEN APPENDECTOMY IN PEDIATRIC PATIENTS –OPERATIVE AND POSTOPERATIVE EXPERIENCE - Toni Risteski; Rozeta Sokolova; Shaban Memeti; Risto Simeonov (My University, 2022)
Objective: Acute appendicitis is very frequently encountered in children. Despite many scientific controversies in supporting classical or laparoscopic appendectomy, there is still no official consensus on this issue. This study aimed to present our experience from the comparison of operative and postoperative effects of laparoscopic and open appendectomy in pediatric patients with acute appendicitis. Materials and methods: The analytical cross-sectional study was conducted at the University Clinic for Pediatric Surgery, Ss. Cyril and Methodius University in Skopje, the Republic of N.Macedonia during the period 2015/2022. The study sample covered 184 hospitalized pediatric patients aged 4-14 years treated with laparoscopic (LA) or open appendectomy (OA). The data of interest included demographic characteristics, and selective operative and postoperative parameters. Results: The average age of the children in LA vs. OA group was 9.63±2.70 with min/max of 4/14 vs. 9.16±2.91 with min/max 2/14 respectively. Postoperative complications were detected in 1 (0.90%) of LA patients and 3 (4.11%) of OA patients with no significant association. Analgesics’ treatment received 57 (51.35%) of the children from LA group and all of the children from OA group. Conversion from LA to OA happen only in 1 (0.54%) child. The evaluation of parents/guardians related to the satisfaction from the cosmetic appearance of the scar the significantly higher level of satisfaction from the scare after LA compared to OA intervention. Conclusions: Laparoscopic appendectomy was found to be feasible and comparable to open approach in terms of operative time and offers advantages over the latter in terms of postoperative pain, length of hospital stay and earlier return of bowel function to normal. It is a safe approach in all types of appendicitis, with an overall better complication profile than OA.
Keywords: acute appendicitis; children; laparoscopic appendectomy; open appendectomy; postoperative effects